Biopaliwa drugiej generacji - Krzysztof Biernat (Studia Ecologiae et Bioethicae)
In this paper clasification and definitions of biofuels for combustion engines, with special focus on UE and U.S demands for fuels is given. Main feedstocks and technologies of biofuel production, also second generation biofuels, are describe, there is also presented current situation in fuels stadarization.